IJSD Volume 2 2012 Scaffolding the Medium - Kappenberg, Claudia; Rosenberg, Douglas (The International Journal of Screendance, 2017)
No abstract available Originally published by Parallel Press, an imprint of the University of Wisconsin-Madison Libraries, as The International Journal of Screendance, Volume 2 (2012), Parallel Press. It is made available here with the kind permission of Parallel Press.